EXPERIENCE WITH APPLICATION OF GEL AND ALGINATE WOUND COVERING IN TREATMENT OF BURNS - A. L. Admakin; V. A. Maksyuta; M. G. Nigmatulin; L. B. Smirnov (Вестник хирургии имени И.И. Грекова, 2018)
Adequate treatment of the burned is not always possible by traditional local conservative methods. Combustologists face considerable difficulties when the patients have non-healing wounds against the background of concomitant diseases or there is a shortage of donor resources for critically burned patients. Results of using wound coverings «Suprasorb» are analyzed in patients with superficial and deep wounds. The clinical course of the wound process, pains during bandage and the dynamics of microbial dissemination of the wounds are assessed.